2017
DOI: 10.1136/bcr-2017-221104
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous valve in valve in the tricuspid position in a patient with Tetralogy of Fallot

Abstract: Here, we describe a case of a successful percutaneous insertion of a transcatheter 29 mm Edwards Sapien XT valve into a tricuspid valve in a patient with repaired tetralogy of fallot.Similar procedures have been performed with the Edwards Sapien valve and Melody valves; however, this is the first case described in the literature of an Edwards Sapien valve used in a patient with Tetralogy of Fallot.With procedural safety being demonstrated, this case illustrates an important alternative treatment option for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Given the short term bene t from valvuloplasty, the patient underwent a percutaneous valve-in-valve procedure with a 29mm Edwards Sapien XT in the existing 31mm Mosaic Valve (true internal diameter 26mm) with resolution of rightsided failure and improvement in diastolic mean gradient across the tricuspid valve from 15mmHg to 4mmHg. The patient was treated with dual antiplatelets for 6 months, followed by aspirin alone, and the details of this procedure have been previously published by the authors 3 .…”
Section: Past Medical Historymentioning
confidence: 99%
“…Given the short term bene t from valvuloplasty, the patient underwent a percutaneous valve-in-valve procedure with a 29mm Edwards Sapien XT in the existing 31mm Mosaic Valve (true internal diameter 26mm) with resolution of rightsided failure and improvement in diastolic mean gradient across the tricuspid valve from 15mmHg to 4mmHg. The patient was treated with dual antiplatelets for 6 months, followed by aspirin alone, and the details of this procedure have been previously published by the authors 3 .…”
Section: Past Medical Historymentioning
confidence: 99%
“…These patients often undergo multiple surgeries, and percutaneous intervention is an attractive option because the procedure can be complicated by multiple sternotomies[ 7 , 8 ]. Challa et al [ 9 ] described a case of successful percutaneous insertion of a transcatheter 29 mm Edwards Sapien XT valve into the tricuspid valve in a patient who underwent TOF repair[ 9 ]. Seckeler et al [ 10 ] reported the case of a high-risk patient with complex adult congenital heart disease who underwent successful percutaneous tricuspid valve-in-ring placement with a SAPIEN 3 valve.…”
Section: Introductionmentioning
confidence: 99%
“…Tricuspid valve dysfunction is a relatively uncommon occurrence, with a higher prevalence in individuals with congenital heart abnormalities, often involving complex patients and frequently quite debilitated. 2,3 Severe tricuspid valve dysfunction and especially severe regurgitation is associated with increased mortality independently from other factors. Surgical tricuspid valve replacement is the main indication for the treatment of severe tricuspid valve dysfunction (regurgitation, stenosis or mixed).…”
mentioning
confidence: 99%
“…2,3 Management of these patients is complicated by the presence of previous sternotomies, and a high surgical morbidity and mortality, which makes a percutaneous approach an appealing option. 2,3 The implantation of percutaneous valves in the tricuspid position is still an off-label indication, but it can be an option to avoid re-interventions on tricuspid bioprosthesis. Here, we describe a case of successful percutaneous tricuspid valve-in-valve procedure, with a 23-mm-Edwards Sapien S3 valve © in a 10 kg boy.…”
mentioning
confidence: 99%